DIVERSITY OF MUSIC GENRES IN SUNDAY SERVICES OF HKBP CHURCH IN MEDAN CITY: THEOLOGICAL, CULTURAL, AND MUSIC MANAGEMENT PERSPECTIVES - Elfrida Yuliana Simamora; Mauly Purba; Pulumun P. Ginting; Junita Batubara (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study explores the diversity of musical genres is a multidimensional phenomenon in the realm of musical arts that reflects the systematic heterogeneity of musical styles, forms, and practices that develop in various cultural, historical, and social contexts. In a theoretical-musical perspective, this diversity is reflected through the differentiation of basic elements of music: such as melody, harmony, rhythm, timbre, texture, form, and dynamics that form the idiomatic characteristics of each genre. This study aims to examine the diversity of HKBP church music genres used in performing songs in Sunday services, to examine the choice of musical genres used in church services in HKBP and to examine church policies towards HKBP church music. The method used is descriptive qualitative with a phenomenological approach, supported by observation, in-depth interviews, and documentation. The theories used include the Theory of Music Diversity, the Theory of Cultural Contact and the Theory of Music Management. The results of the study show that the diversity of musical genres has undergone significant changes in the musical structure of each HKBP church, the use of modern instruments, but still maintains traditional elements such as hymn music (organ). The new music style (genre) that was formed was the result of Cultural Contact of HKBP church musicians with the demands of the times, the tastes of musicians or congregations and contemporary performance spaces. The music policy in each HKBP church is different because the musicians in each church are not trained and practices in the field are different, the leadership of the Pastor in the church does not all understand HKBP church music. For musicians accompanying Sunday services in HKBP churches, knowing the many music genres is due to the freedom to appreciate playing music because there is no written HKBP music policy but the policy exists through Oral Tradition. This study contributes to the development of HKBP church music policies that are adaptive to cultural and generational contexts, while preserving the roots of Lutheran liturgical tradition.